On the Boundedness of an Economy with Externalities - Osana, Hiroaki (Review of Economic Studies, 1973)
Journal Article On the Boundedness of an Economy with Externalities Get access Hiroaki Osana Hiroaki Osana Keio University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 3, July 1973, Pages 321–331, https://doi.org/10.2307/2296453 Published: 01 July 1973